Robert Stanton’s Structuralist Analysis of Mustafa Mahmud’s Az-Zaʿīm: Implications for Arabic Pedagogy and Character Education - Sayyidah Khoizuroonah; Anisa Dwi Nurchayati; Mukhammad Kamil Pribadi (Lingu, 2026)
Purpose – This study investigates the intrinsic structural components of Mustafa Mahmud’s drama Az-Zaʿīm and evaluates its pedagogical utility within the framework of Arabic language instruction. Utilizing Robert Stanton’s structuralist theory, the research aims to examine how characters, plot, setting, theme, and moral values are integrated to construct a narrative focused on social justice and resistance against Ottoman hegemony. Design/methods/approach – The study employs a qualitative approach with a descriptive-analytical method, utilizing content analysis to interpret primary textual data and secondary scholarly sources. Findings – The findings reveal a sophisticated interplay between elements, where the linear-chronological plot and symbolic spatio-temporal settings elevate the protagonist into an emblem of dignity and resistance. The thematic core centers on the pursuit of socio-political equality, articulated through narrative dialogues that serve as a vehicle for ethical instruction. While limited by its singular focus on a specific work and framework, the study recommends future comparative research and empirical investigations into classroom implementation to quantify the impact of literary analysis on students' moral and linguistic development. Research Implications – The analysis highlights significant implications for Arabic Applied Linguistics, suggesting that the text serves as an authentic resource for developing Higher-Order Thinking Skills (HOTS) and communicative competence. By bridging the gap between linguistic proficiency and cultural literacy, the drama facilitates character education through the internalization of values such as loyalty and justice.